2017
DOI: 10.1108/ecam-03-2016-0084
|View full text |Cite
|
Sign up to set email alerts
|

Modeling schedule overrun and cost escalation percentages of highway projects using fuzzy approach

Abstract: Purpose Modeling represents the art of translating problems from an application area into tractable mathematical formulations whose theoretical and numerical analysis provides insight, answers and guidance useful for the originating application. The purpose of this paper is to determine the causal causes of schedule overrun and cost escalation of highway projects in Egypt in order to be used as independents variables in mathematical models for predicting the percentages of schedule overrun and cost escalation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Moreover, another research has been done by Ismail et al (2014) which interviews were conducted among experts and the factors of cost overrun identified were [18] According to Waithera and Susan (2017) studies, the main and major causes of cost overrun in construction of road projects in Kenya are project schedule, poor project management, project scope, government policies, resources and contract management [19]. A questionnaire survey was conducted by Abu El-Maaty et al (2017) to know the main causes of cost overrun in road project were technical staff at contractor, inadequate planning and preparation of project planning and execution [20].…”
Section: Cost Overrunmentioning
confidence: 99%
“…Moreover, another research has been done by Ismail et al (2014) which interviews were conducted among experts and the factors of cost overrun identified were [18] According to Waithera and Susan (2017) studies, the main and major causes of cost overrun in construction of road projects in Kenya are project schedule, poor project management, project scope, government policies, resources and contract management [19]. A questionnaire survey was conducted by Abu El-Maaty et al (2017) to know the main causes of cost overrun in road project were technical staff at contractor, inadequate planning and preparation of project planning and execution [20].…”
Section: Cost Overrunmentioning
confidence: 99%
“…Again, Durdyev et al 's (2017) study identified inadequate material on-site and site hazard risks due to a lack of safety measures as the leading causes of project delays in Cambodia. Abu El-Maaty et al (2017) established that factors primarily affecting the delay of projects were construction material shortage and changes of the type of material during project execution. Again, Kazemi et al (2021) and Famiyeh et al (2017) mentioned equipment inefficiencies, contractor feeble project management and contractors underestimating project complexity contributing to project delays.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Sharma and Goyal (2019) developed a fuzzy based model to estimate the risk magnitude of 55 important risk factors causing cost overrun in Indian construction projects. Models of cost overrun prediction based on the fuzzy logic were also developed by Knight and Fayek (2002), Dikmen et al (2007), Phama et al (2020), Amadi and Higham (2017), El-Maaty et al (2017), Kim et al (2018), Plebankiewicz (2018), Plebankiewicz and Wieczorek (2020), Islam et al (2019).…”
Section: Costmentioning
confidence: 99%